(untitled) (The Journal of Psychology and Sociology, 2017)
On the one hand domestic violence is one of the most serious and widespread social problem of our society which Unfortunately most victims of these violence are women. On the second hand domestic violence has negative effects on children personality development, which made it notable. This article is result of analyzing of many articles and books which published by Human rights organization and other organizations which work for women rights. Through study of those books and articles we can find out that domestic violence special violence against women which is the worst type of violence that can be destroyed the infrastructure of families and society, are very widespread. Violence against women in Very heinous for different economic and social reasons in different forms (physical violence, sexual violence, verbal and psychological violence, and economic violence) occur in different parts of Afghani stan which physical violence is very common. Despite government of Afghanistan with corporation of international organization has ratified many law like: law on elimi nation of violence against women which ratified based on article 54 Afghanistan con stitution law in 2009 in four chapter and 44 articles to prevent or keep away women from violence but unfortunately those rules and laws just on the paper they are not applied and government does not deal with perpetrators of violence. In article of that law mentioned all actions which is considered Violence against women.1. Sexual assault; 2. Forced prostitution; 3. Recording the identity of the victim and publishing it in a way that damages her personality; 4. Burning, using chemicals or other danger ous substances; 5. Forcing one to burn herself or to commit suicide or using poison or other dangerous substances; 6. Causing injury or disability; 7. Beating; 8. Selling and buying women for the purpose of or on the pretext of marriage; 9. Giving; 10. Forced marriage; 11. Prohibiting from the right of marriage or right to choose spouse; 12. Underage marriage; 13. Abusing, humiliating, intimidating; 14. Harassment/persecu tion; 15. Forced isolation; 16. Forced addiction; 17. Depriving from inheritance; 18. Prohibiting to access personal property; 19. Prohibiting from the right to education, work and access to health services; 20. Forced labor; 21. Marrying more than one wife without observing Article 86 of Civil Code; and, 22. Denial of relationship.